Intimasi Pelatih-Atlet dan Kecemasan Bertanding Pada Atlet Bola Voli Putri - Jenny Indra Sabilla; Miftakhul Jannah (Universitas Negeri Surabaya, 2017)
Coaches can recognize their athletes deeply by building intimacy. Intimacy leads to the disclosure of personal matters to other people. Athletes who have intimacy with their coaches will talk openly about themselves. By intimacy, coaches can appropriately provide load tasks according to the abilities of athletes and give assistances to the athletes during competition. This research aims to determine the correlation of anxiety to competition and intimacy of coach-athlete in volley ball athletes. This was a correlation quantitative methods with parametric data. 60 volley ball student club athletesin Universitas Negeri Surabaya (Unesa)were involved in this study. Two instruments used were anxiety to competition and coach-athlete intimacy scales. Data were analyzed using Pearsons product moment correlation. The results shows the signivicant value (p) of 0.000 (p < 0,05) which means the hypothesis of this study is accepted: there is significant correlation between athlete-coach intimacy and athletes anxiety to competition. The result also shows the correlation coefficient of -0,661 which indicates that the correlation is negative. It can be concluded from this result that athletes who have high coach-athlete intimacy will feel less anxious to competition.Abstrak: Intimasi mengarah pada keterbukaan pribadi dengan orang lain, pelatih dapat mengenal atlet lebih dalam dan pelatih bisa dengan tepat memberikan beban tugas yang sesuai dengan kemampuan atletnya. Adanya intimasi dengan pelatih, membantu atlet menurunkan kecemasan bertanding. Penelitian ini bertujuan untuk menguji hubungan antara kecemasan bertanding dan intimasi pelatih-atlet pada atlet bola voli dengan menggunakan metode kuantitatif korelasional. Subjek penelitian adalah 60 orang mahasiswa UKM bolavoli Unesa. Instrumen yang digunakan adalah skala kecemasan bertanding dan skala intimasi pelatih-atlet. Analisis data yang digunakan dalam penelitian ini adalah korelasi pearson product moment. Hasil penelitian data menunjukkan nilai koefisien korelasi sebesar -0,661. Atlet yang memiliki intimasi pelatih-atlet akan merasa mendapat dukungan dari pelatihnya sehingga atlet merasa memiliki persepsi diri positif dan merasa nyaman.